Leveraging Knowledge Management for Public Sector Organizational Performance: The Mediating Role of Learning Organization - Mandon Febriyanto; Nidya Dudija (Indonesian Journal of Advanced Research, 2026)
Government agencies need to leverage the intersection of knowledge management (KM) and learning organization (LO) principles to optimize overall organizational performance (OP). Focusing on the Financial Education and Training Agency (BPPK), this research evaluates how the LO serves as a bridge, mediating the impact of KM on OP. A quantitative approach was employed, surveying 276 employees through SEM-PLS analysis. Results indicated that KM substantially improved outcomes through both straightforward effects and intervening processes facilitated by the LO. As a significant partial mediator, LO demonstrated that knowledge assets required a robust learning culture to maximize institutional efficiency. Consequently, public institutions should integrate KM with continuous learning initiatives to foster an agile organization and improve public service delivery.